Minimally Invasive Interventional Therapy for Liver Abscess with Bloodstream Infection Caused by a Fishbone Perforation of the Stomach Wall: A Case Report - Zhang A; Wei W; Pei R; Li X; Yang J (Infection and Drug Resistance)
Aiping Zhang,1,* Wei Wei,2,* Renguang Pei,3 Xiaoning Li,4 Jinsun Yang1 1Department of Infectious Diseases, Yijishan Hospital of Wannan Medical College, Wuhu, Anhui, 241001, People’s Republic of China; 2Department of Sonography, Yijishan Hospital of Wannan Medical College, Wuhu, Anhui, 241001, People’s Republic of China; 3Department of Interventional, Yijishan Hospital of Wannan Medical College, Wuhu, Anhui, 241001, People’s Republic of China; 4Department of Medical Laboratory, Yijishan Hospital of Wannan Medical College, Wuhu, Anhui, 241001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinsun Yang, Department of Infectious Diseases, Yijishan Hospital of Wannan Medical College, Zheshan West Road, Jinghu District, Wuhu, Anhui, 241001, People’s Republic of China, Tel/Fax +86-553-5739406, Email yangjinsun999999@163.comAbstract: Liver abscess is a common disease in clinical practice, whereas liver abscess resulting from the penetration of a fishbone through the gastric wall is infrequently observed. Herein, we present the case of a 67-year-old male patient of Chinese origin. The patient had been experiencing a fever for 10 days and was subsequently admitted to the hospital. Laboratory investigations revealed elevated levels of inflammatory markers, with blood cultures identifying Streptococcus anginosus (S. anginosus). Imaging studies including abdominal ultrasound and contrast-enhanced computerized tomography (CT) confirmed the presence of an abscess in the left hepatic lobe, along with foreign bodies located within both the liver parenchyma and the gastric wall. Based on the patient’s medical history and imaging results, the ultimate diagnosis indicated that a fishbone had perforated the stomach wall, resulting in an intrahepatic abscess and subsequent bacteremia. The patient underwent anti-infection therapy followed by a minimally invasive interventional technique to remove the fishbone. This case shows that interventional technique presents an alternative treatment approach for managing foreign bodies within the liver.Keywords: liver abscess, fishbone, Streptococcus anginosus, minimally invasive interventional technique